Pengaruh Latihan Range Of Motion (ROM) Pasif Terhadap Kekuatan Otot dan Rentang Gerak Sendi Ekstremitas Pada Pasien Pasca Stroke. - Daulay, Nanda Masraini; Hidayah, Arinil (Jurnal Kesehatan Ilmiah Aufa Royhan, 2021)
Stroke is a neurogenic disease that causes disorders of brain function both locally and globally and the most common cause of disability. Patients should get a good handling to prevent physical and mental disability. The purpose of this research was determine the effect of passive Range Of Motion (ROM) exercise on muscle strength and range of motion of limb joints in post-stroke patients. The research design was a quasi experiment with a one group pretest and post test design approach. The research was conducted to 17 out patients of UPT RSUD South Tapanuli Regency. Data analysis used the wilcoxon test. The result indicated the effect of passive ROM exercise on muscle strength with p-value of 0,001 in the upper extremity and p-value of 0,001 in the lower extremity. They also showed the effect of passive ROM exercise on the range of joint motion with p-value of 0,001 in the upper extremity and p-value of 0,001 in the lower extremity. ROM exercise could be recommended by the Nurse as a rehabilitation program for handling post-stroke patients.